Efektivitas Penggunaan QRIS Bank BNI terhadap Kemudahan dan Efisiensi Transaksi di Kantin UNTAG Surabaya - Ida Ayu Nuh Kartini; Diah Ayu Susilaningtias; Jeslin Cecelia Thunggal; Revalia Wulan Suryani; Teresya Dwigantara Wega (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study analyzes the effectiveness of using BNI Bank’s QRIS in improving transaction convenience and efficiency at the canteen of Universitas 17 Agustus 1945 (UNTAG) Surabaya. The research was conducted by a team led by Ida Ayu Nuh Kartini, S.E., M.M., together with students of the Management Study Program, during November–December 2025. The rapid development of digital banking has encouraged the adoption of QRIS as a standardized non-cash payment system regulated by Bank Indonesia. This study aims to examine the level of QRIS BNI utilization, assess ease of use (application access and QR code scanning), and evaluate transaction efficiency, including time savings, queue reduction, and error minimization. A descriptive quantitative approach was employed using a survey method with a five-point Likert scale questionnaire distributed to 36 respondents consisting of students, lecturers, and administrative staff who had used QRIS at the canteen. Primary data were analyzed descriptively using averages and percentages, supported by relevant literature. The results show that QRIS is perceived as highly effective, with scores above 90% for ease of use (95%), transaction speed (92.78%), reduction of change-related issues (97.78%), support for digitalization (97.22%), and security (91.11%). The main limitation identified is dependence on internet connectivity (85%). Overall, respondents strongly support the full implementation of non-cash payment systems at the campus canteen.